Experimental Approaches to Transforming Academic Library Print Collections - Laster, Shari; McAllister, Lorrie; Pattni, Emily; Dang, Tammy (Library resources & technical services, 2025)
As academic libraries renovate their facilities, often seeking to reduce print collection footprints within public-facing service areas, there is an opportunity to develop new design strategies and methods for print curation that meet the needs of the communities served by these libraries. In alignment with a major renovation, ASU Library developed a community-focused approach to academic library print collections, providing opportunities to engage and inspire them to create new knowledge and foster an overall sense of belonging. As part of a grant-funded program, ASU Library created eight experimental projects that explored the ways in which people engage with books in print, which led to new collaborative methods for developing print collections for the post-renovation reopening of Hayden Library, ASU's largest library on Tempe campus. This work has resulted in improved knowledge of effective workflows and communication strategies to enhance engagement with print collections, becoming a signature library program to co-develop inclusive featured browsing collections with university and community partners.